ARTIFICIAL INTELLIGENCE AND THE TRANSFORMATION OF SOCIAL SCIENCE EDUCATION IN THE SOCIETY 5.0 ERA: Bahasa Indonesia - Muhammad Mona Adha; Pujiati; Irma Lusi Nugraheni; Nikki Tri Sakung; Dayu Rika Perdana (UNDIKMA, 2026)
This study aims to examine the enhancement of literacy and competence in the use of Artificial Intelligence (AI) in the transformation of Social Sciences (IPS) learning in the Society 5.0 era. The background to this study is the still limited understanding and practical skills of students and lecturers on the Master’s Programme in Social Sciences Education at the University of Lampung in integrating AI into the design, implementation and evaluation of Social Sciences learning. The study employed a quantitative approach using a one-group pre-test–post-test pre-experimental design involving 15 participants, comprising 8 students from the 2025 intake and 7 lecturers from the Master’s Programme in Social Sciences Education. The intervention, comprising training and guidance on the development of AI-based social studies teaching materials and learning resources, was carried out over a full day on 8 June 2026. An assessment instrument comprising 15 multiple-choice questions based on Higher Order Thinking Skills (C4, C5, C6) was used to measure AI literacy and learning transformation abilities before and after the intervention. The research results showed that the average score increased from 54.47 (pre-test) to 86.73 (post-test), with an average N-Gain of 0.72 in the high category. A paired t-test yielded t = 17.93; df = 14; p = 0.000, indicating a significant difference between pre- and post-training scores. It was concluded that training in the use of AI effectively enhances the competence of students and lecturers in designing social studies learning that is adaptive to technological developments, whilst also contributing to the strengthening of the quality of social studies education in the Society 5.0 era.